Practical security in commerce and industry - Oliver, Eric.; Wilson, John (Epping : Gower Press, 1974)
In this edition greater emphasis was given to computer security and industrial and commercial espionage and new chapters were included for example on commercial fraud, planning for emergencies such as bomb threats and the risks to security through drug addiction. Although the law and practice described in this book apply to the United Kingdom, they are not likely to differ in material particulars from those of other countries because, of course, security measures have international application.
Includes bibliographical references and index.
hza 26/07/2018
Loan
Keywords: Industries; Retail trade; Security systems